Evaluación microbiológica de la carne bovina en mercados y camal del cantón Machala provincia de El Oro - Vargas Zambrano, Michel Fabián (2015)
The aim of this study was to asses the microbiological quality of raw bovine meat at two markets and one slaughterhouse located in Machala, Province of El Oro. Fresh meat samples were daily collected between the 25 de Junio market and central market, samples were also collected from the municipal slaughterhouse inmediately after the slaughter and splitting. Meat Samples were subjected to total viable count according to the INEN NTE 1529-5 procedure, E. coli and S. aureus detection. Mean TVC value for the 25 Junio market and Central market were 7.30, 6.87 log CFU/g respectively, from this study was also found that 33.33% for the first market and 23.81% for the second did not achieve the microbiological limits proposed by the RTE INEN 056 normative, TVC value was 4.67 log CFU/g for Municipal Slaughterhouse founding that initial contamination at abattoir level was highly significant (p<0.05) than the markets, in adittion Escherichia coli was detected in 100% of the samples from the two markets and was not found in raw meat from the slaughterhouse. A 100% presence of Staphylococcus aureus was also found from the markets and 0% from slaughterhouse. It is concluded that microbioal load is high due to an elevated initial count at slaughterhouse, poor hygiene, trasnportation and manipulation practices insinuating short shelf-life and risk for potential foodborne diseases.